Disparities of health service for the poor in the coastal area: does Universal health coverage reduce disparities? - Md. Hafiz Iqbal (Taylor & Francis Group, 2019)
Background & Objective: Poor people, in general, get poor quality of health services. The situation is very much worsening for the poor who live in the remote areas in the coastal belt of Bangladesh as health care facilities and services are often less complete, farther away, and therefore most costly to reach than in urban hospitals and physician. Ensure of better health service for the poor, it is essential to examine the effectiveness of Universal Health Coverage (UHC). This study sets its objectives to evaluate the health service for the poor in the coastal area of Bangladesh and develop an approach of management strategy. Methods: This study followed a two-stage cluster sampling technique and carried out a household survey through the open-ended questionnaire. In addition, the study applied the logistic regression model to generate empirically supported assessments. Results: Result from the disparity rate ratio (DRR) revealed that there is a big health care disparity of different income groups like poor and rich. Furthermore, results from the model demonstrated that Medicaid, Medicare, Social Health Insurance, Telemedicine and Capitation under the provision Universal Health Coverage (UHC) are statistically significant compared to reduce the health care disparity. Conclusion: UHC becomes a critical issue for improved and quality health care system for all the groups especially, the poor in coastal Bangladesh. This study showed that Medicaid, Medicare and Social Health Insurance and Capitation perform well to provide better health care facilities for all.